2017
DOI: 10.3310/pgfar05020
|View full text |Cite
|
Sign up to set email alerts
|

A community-based primary prevention programme for type 2 diabetes mellitus integrating identification and lifestyle intervention for prevention: a cluster randomised controlled trial

Abstract: BackgroundPrevention of type 2 diabetes mellitus (T2DM) is a global priority; however, there is a lack of evidence investigating how to effectively translate prevention research into a primary care setting.Objectives(1) To develop and validate a risk score to identify individuals at high risk of T2DM in the UK; and (2) to establish whether or not a structured education programme targeting lifestyle and behaviour change was clinically effective and cost-effective at preventing progression to T2DM in people with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 205 publications
0
19
0
1
Order By: Relevance
“…The study design does not permit us to identify reasons for these small differences. However, some qualitative work conducted as part of the study suggests that patients receiving the structured education programme felt they had an increased understanding of the nature and implications of their diagnosis, and better understood key messages about lifestyle changes with regard to diet and physical activity 24. This may have resulted in higher utility levels.…”
Section: Discussionmentioning
confidence: 99%
“…The study design does not permit us to identify reasons for these small differences. However, some qualitative work conducted as part of the study suggests that patients receiving the structured education programme felt they had an increased understanding of the nature and implications of their diagnosis, and better understood key messages about lifestyle changes with regard to diet and physical activity 24. This may have resulted in higher utility levels.…”
Section: Discussionmentioning
confidence: 99%
“…Several interventions have been suggested for prevention and control of diabetes. Although the effectiveness and cost-effectiveness of all interventions are not promising, there is evidence of several successful experiences around the world (Davies et al 2017 ; Sun et al 2017 ). For example, the National Diabetes Prevention Program showed successful changes in determinants of diabetes (Ely et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors found a 26% reduction in the risk of type 2 DM of those who received the intervention compared with the standard care. They found no statistical significance, which suggests that the effectiveness of all interventions is not promising [17].…”
Section: Discussionmentioning
confidence: 96%
“…The patients had a median vintage on PD of 13 months (4-26), without differences between DM and No-DM. In addition, there were no differences in the glucose concentration used in the dialysis solutions, but DM patients were less likely to be on automated peritoneal dialysis (APD) modality (p = 0.016), and the median dwell time was 16 h (QR [16][17][18][19][20][21][22][23][24]. There were no differences in the D/P creatinine or the history of peritonitis between patients.…”
Section: Dialysis Characteristicsmentioning
confidence: 98%